Mendelian Genetics and Its Applications in Understanding Genetic Diseases - Ahmed Rashid Tubena; Sabah Attwan Kazi; Salim Dakhil Rashid; Ahmed Rashid Tubena; Sabah Attwan Kazi; Salim Dakhil Rashid (Jurnal MIPA dan Pembelajarannya, 2026)
This research topic explains the fundamental principles of the Mendelian genetics and how they have been of the fundamental importance in explaining the ability to inherit genetic diseases in human beings. The laws of segregation and independent assortment, which were developed by Gregor Mendel in the nineteenth century, are still the foundations of classical and modern medical genetics. According to qualitative descriptive approach, the study applies scientific knowledge to investigate how the principles deal with the transmission of monogenic disorders, including autosomal dominant, autosomal recessive and X-linked inheritance. The findings indicate that Mendelian models are required to comprehend the way to establish the carrier, predict the danger of the disease in the further generations and provide appropriate genetic counselling. The example of diseases with a great deal of literature such as Cystic Fibrosis, Sickle Cell Disease and Huntington Disease can serve as examples of how these laws can be applied in clinical diagnosis. The paper also analyses the fusion of classical genetics and the present genomic technology such as DNA sequencing and the Human Genome Project. Despite the fact that more comprehensive processes of environmental and multi-gene interaction are used with complex polygenic disorders, Mendelian genetics continues to provide the primary theoretical framework of addressing hereditary illnesses. The authors come to the conclusion that the collaboration between the Mendelian and molecular biology is critical to the future of early diagnosis and preventive medicine and particular treatment procedures.